2018
DOI: 10.3390/rs10050761
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Classification Algorithm for Early Weed Detection in Row-Crops by Combining Spatial and Spectral Information

Abstract: Abstract:In agriculture, reducing herbicide use is a challenge to reduce health and environmental risks while maintaining production yield and quality. Site-specific weed management is a promising way to reach this objective but requires efficient weed detection methods. In this paper, an automatic image processing has been developed to discriminate between crop and weed pixels combining spatial and spectral information extracted from four-band multispectral images. Image data was captured at 3 m above ground,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 48 publications
0
40
0
1
Order By: Relevance
“…However, this technique requires precise modeling in terms of texture, 3D models, and light conditions. In [34], an automatic image processing method was developed to discriminate between crop and weed pixels by combining spatial and spectral information extracted from four-band multispectral images. Image data were captured at 3 m above ground with a camera mounted on a manually held pole.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique requires precise modeling in terms of texture, 3D models, and light conditions. In [34], an automatic image processing method was developed to discriminate between crop and weed pixels by combining spatial and spectral information extracted from four-band multispectral images. Image data were captured at 3 m above ground with a camera mounted on a manually held pole.…”
Section: Related Workmentioning
confidence: 99%
“…This method was applied to only one field, but we have found that the feature selection approach, even with random forest, is not robust when the field or crop type changes. In [34], an automatic image processing method was developed to discriminate between crop and weed pixels on images acquired by a camera mounted on a manually held pole. The authors combined spatial and spectral information extracted from four-band multispectral images.…”
Section: Weed Detectionmentioning
confidence: 99%
“…Machine learning and image processing have proved their utility in diverse fields. Especially in the field of plant phenotyping [2][3][4][5][6][7], these tools have laid a strong foundation in detecting multiple crop diseases [8] as well as making sense of disease severity without the need for any additional human supervision [8], crop/weed discrimination [9][10][11][12], canopy/individual extraction [13,14], fruit counting/flowering [15][16][17], and head/ear/panicle counting [18][19][20]. Our hypothesis is that machine learning and image processing along with unmanned aerial vehicles (UAV) based photogrammetry is a reliable alternative to the laborintensive sorghum head survey in the field [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…All these papers describe applications on vertical pruning systems (VPS), the most widespread class of training systems used in quality viticulture, which presents a discontinuous spatial layout with vegetated rows alternating with soil [54,55]. In these cases, spatial analysis of remote sensing images requires separation of the canopy from bare soil, shadows, and green cover, which can be achieved with advanced filtering techniques for canopy extraction [56][57][58][59][60]. Many authors suggest unsupervised filtering techniques in a vineyard based on a canopy height model (CHM) derived from a digital elevation model (DEM) [51,53], geometric structure by texture analysis [61,62], 3D point cloud [63], automatic threshold on color distribution in RGB [64], different color spaces such as HSV (hue, saturation, value), or L*a*b* (L* for the lightness from black to white, a* from green to red and b* from blue to yellow) [65].…”
Section: Introductionmentioning
confidence: 99%